PAPR Comparison of OFDMA, LFDMA and IFDMAfor LTE, Wireless Transmission - Khelil, Abdellatif; Slimani, Djamel (University of Eloued جامعة الوادي, 2014)
LTE 3GPP has adopted Orthogonal Frequency Division Multiplexing (OFDM) for the downlink transmission. OFDM meets the LTE requirement for spectrum flexibility and anables cost efficient solutions for very wide carriers with peak to average power ratio (PAPR) of the transmitting signals has limited its application. This high PAPR causes interference when the OFDM signals are passed through an amplifier which does not have enough linear. In this paper we investigate a DFT spreading PAPR reduction for Interleaved SC-FDMA (IFDMA) and Localized SC-FDMA (LFDMA) compared with OFDMA without DFT-spreading. Simulation result show that OFDMA exhibits a higher PAPR compared to SC-FDMA (LFDMA and IFDMA). This low PAPR makes the SC-FDMA the preferred technology for the LTE uplink transmission.
international Congress on Telecommunicatisnand Application,l4 23-24 Avril 2014 université Bejaia
Keywords: OFDMA, SC FDMA, LFDMA, IFDMA, PAPR, LTE